Spectroscopic studies of the inclusion compound of lisinopril withβ-cyclodextrin. Issue 3 (2009) - Olaru Olaru, Alexandra Alexandra; Borodi Borodi, Gh. Gh.; Kacsó Kacsó, Iren Iren; Vasilescu Vasilescu, M. M.; Bratu Bratu, I. I.; Cozar Cozar, O. O.
Abstract : The inclusion compounds of lisinopril with β -cyclodextrin, prepared by different methods: kneading, co-precipitation and freeze-drying were investigated by XRD, FTIR, DSC and solid-state NMR techniques. It was established by these methods that the complexation process was successfully. The degree of crystallinity for the product obtained by kneading was also determined. The kneaded product has a certain crystallinity degree, so it is possible that the inclusion process is less effective in this case. In the case of freeze-dried and co-precipitated products only amorphous phase exists, i.e. the complexation was produced with a higher efficiency.